2019
DOI: 10.1021/jacs.8b10407
|View full text |Cite|
|
Sign up to set email alerts
|

Graphene Nanoribbons Derived from Zigzag Edge-Encased Poly(para-2,9-dibenzo[bc,kl]coronenylene) Polymer Chains

Abstract: In this work, we demonstrate the bottom-up on-surface synthesis of poly­(para-dibenzo­[bc,kl]-coronenylene) (PPDBC), a zigzag edge-encased analog of poly­(para-phenylene) (PPP), and its lateral fusion into zigzag edge-extended graphene nanoribbons (zeeGNRs). Toward this end, we designed a dihalogenated di­(meta-xylyl)­anthracene monomer displaying strategic methyl groups at the substituted phenyl ring and investigated its applicability as precursor in the thermally induced surface-assisted polymerization and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 23 publications
1
45
0
3
Order By: Relevance
“…e) Synthetic route of zeeGNRs. Reproduced with permission . Copyright 2019, American Chemical Society.…”
Section: Crucial Elements and Growth Procedures Of Gnrsmentioning
confidence: 99%
See 1 more Smart Citation
“…e) Synthetic route of zeeGNRs. Reproduced with permission . Copyright 2019, American Chemical Society.…”
Section: Crucial Elements and Growth Procedures Of Gnrsmentioning
confidence: 99%
“…It can be visually observed that the precursor directly determines the ribbons' periphery structure (cove edge). With precise design of the precursor, zigzag edge‐extended GNRs (zeeGNRs) as another novel structure (Figure e) were recently explored by Beyer et al Other than using one type of precursor, two or more kinds of building blocks can be used in combination to grow various GNR heterojunctions. Gröning et al used a single precursor and a combination of two precursors to prepare various types of GNRs (Figure f) .…”
Section: Crucial Elements and Growth Procedures Of Gnrsmentioning
confidence: 99%
“…Similar to NBN‐ZGNR1, the nitrogen and boron atoms were clearly unveiled in NBN‐ZGNR2 by nc‐AFM measurements (Figure f). Due to the NBN edge doping, these two GNRs featured stable zigzag edges in which no further reaction such as edge fusing was observed after thermal annealing, in contrast to the pristine carbon‐based ZGNRs …”
Section: Figurementioning
confidence: 99%
“…Recently, new type zigzag edge‐extended GNRs with a width of 9 to 11 carbon atoms was derived from zigzag edge‐encased poly( para ‐2,9‐dibenzo[ bc , kl ]coronenylene) polymer chains. These GNRs exhibited a high ratio of zigzag (67 %) to armchair (25 %) edge segments . Furthermore, the addition of heteroatom dopants into the GNRs represents another efficient approach to modulate the band structure and electronic properties of the GNRs.…”
Section: Molecular Reactions: Formation Of Chemical Bondsmentioning
confidence: 99%